Analisis Dampak Serangan Blackhole dan Jellyfish terhadap Protokol Routing Ad-Hoc on Demand Distance Vector (AODV) dengan Model Mobilitas Random pada VANET - Muhamad Alfarisi; Heru Nurwarsito (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
In this era, information technology is growing rapidly and applied to almost aspects of life, including transportation. One of the applied technologies is the Vehicular Ad-Hoc Network (VANET). VANET defines as a smart transportation system, where a vehicle communicates with other vehicles to exchange information and recognizes road conditions simultaneosly in real time. VANET network is an ad-hoc network that does not have a fixed infrastructure and a rapidly changing network topology. This makes VANET network security vulnerable to various attacks both from inside and outside the network. This paper is intended to explain several comparison analysis of the AODV routing protokol without any attacks, with Blackhole and Jellyfish attacks, and was carried out with various speed of the node, that contains 80, 100, 120, 150, 180, and 220 km/hour. This research is simulated using Network Simulator 2 to model the network and use random mobility on nodes. The analysis is reviewed by using QoS parameters, such as Packet Delivery Ratio, Throughput, and Delay. The results of the simulation shows that the scenario of changes in speed of the node affects the performance of the VANET network. In normal scenario without any attacks, the highest PDR value is 98.00%, the Throughput is 128.16 kbps and the Delay is 39.05 ms. In scenario with the Blackhole attacks, it shows the highest PDR value is 64.25%, the Throughput is 84.03 kbps and the Delay is 521.14 ms. Furthermore, there is a scenario with Jellyfish attack, the highest PDR value is 61.39%, Throughput is 80.28 kbps and Delay is 641.47 ms. This can be concluded that the addition of attacks on the AODV routing protokol can affect its performance, as evidenced by the decrease in QoS quality on the VANET network that has been built.